PERANCANGAN APLIKASI PELAPORAN KEGIATAN UKM TARI DI UNIVERSITAS LIA DENGAN METODE AGILE - Ariya Pannadhitthana Candra; Murniasih, Intan (Nusantara Hasana Journal, 2025)
Dance UKM stands for Maahasiswa Dance Activity Unit. Dance UKM is a forum for student organizations in a university that accommodates and channels students' interests and talents in the field of dance arts, both traditional and modern. Dance UKM at LIA University is a means for students to develop their talent and dance skills, deepen their knowledge of various types of dance (traditional, modern), which are staged to preserve culture through certain events held at LIA University. This study discusses the design of the application for reporting the activities of the Dance Student Activity Unit (UKM) at LIA University using the Agile method. The purpose of this research is to develop applications that can simplify the process of reporting activities, increase collaboration between members, and accelerate decision-making in organizations. The Agile method was chosen for its ability to adapt to changing user needs and provide quick feedback in each iteration of development. The application development process goes through several phases, including planning, iterative development, testing, and evaluation. The result of this research is an application prototype equipped with features such as filling out activity reports, member management, and activity notifications. Trial apps show that users find it easier to report and access activity information. This research is expected to make a positive contribution to the development of applications in the SME environment and improve the efficiency of reporting activities at LIA University.